2023
DOI: 10.1039/d3tb01573d
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of biomimicking radially graded scaffolds via digital light processing 3D printing for bone regeneration

Yue Wang,
Shangsi Chen,
Haowen Liang
et al.

Abstract: Four types of biomimicking radially graded scaffolds were designed and fabricated via digital light processing 3D printing. Graded gyroid–gyroid scaffolds exhibited better dimensional accuracy, compressive property, and cell proliferation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Wang et al 38 showed that the graded porous scaffold had a greater compressive toughness and elastic modulus, and that the high-porosity uniform porous scaffold’s compression performance was comparable to that of the tibial spongy bone made of pork. Wang et al 76 reached similar conclusions.…”
Section: Wall Thicknessmentioning
confidence: 58%
See 1 more Smart Citation
“…Wang et al 38 showed that the graded porous scaffold had a greater compressive toughness and elastic modulus, and that the high-porosity uniform porous scaffold’s compression performance was comparable to that of the tibial spongy bone made of pork. Wang et al 76 reached similar conclusions.…”
Section: Wall Thicknessmentioning
confidence: 58%
“…This is because the preparation process has not yet reached the ideal requirements, which requires us to continuously improve the technology and overcome the process limits of 3D printing. 72 , 76 , 100 102 …”
Section: Limitationsmentioning
confidence: 99%